Research Progress on Harmful Products from Maillard Reaction in Dairy Products: Generation Pathways, Detection Methods, and Control Strategies - XU Wenlong, XIE Yijia, PAN Yang, LIAO Lijuan, HUANG Min, YANG Yinxi, WU Yongtai, LI Bing (Shipin Kexue)
The Maillard reaction imparts appealing aroma, color and texture to foods such as bread and coffee; however, in milk and dairy products, the Maillard reaction decreases their nutritional value and generates various harmful compounds, including furosine, furfural, and advanced glycation end-products (AGEs), which are associated with chronic diseases in humans. Understanding the formation mechanisms of harmful Maillard reaction products in dairy products and establishing control methods for these compounds are crucial for improving the quality of dairy products. This article elaborates on the biohazardous nature of harmful Maillard reaction products in dairy products, and focuses on the formation pathways of furosine, 5-hydroxymethylfurfural, and AGEs. Furthermore, the advantages and disadvantages of the methods used for the detection of harmful products from Maillard reaction are reviewed, as well as recent advances in the area. Lastly, this review highlights the current strategies for controlling harmful products from Maillard reaction in dairy products. The aim of this paper is to provide scientific guidance for monitoring and controlling harmful products of Maillard reaction in dairy products.